2001
DOI: 10.3758/bf03206384
|View full text |Cite
|
Sign up to set email alerts
|

The perceptual aspect of skilled performance in chess: Evidence from eye movements

Abstract: One of the most fascinating and impressive aspects of skilled performance is the ability of the experienced eye to encode at a glance the essence of briefly presented stimulus material, which is related to the domain of expertise (henceforth, domain-specific knowledge). For example, Kundel and Nodine (1975) showed expert radiologists X-ray films for 200 msec. The experts were able to detect and name 70% of the abnormalities in the films.Crucial to this process of rapid perception, particularly for visual displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
162
2
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(187 citation statements)
references
References 26 publications
18
162
2
5
Order By: Relevance
“…These studies showed that experts possess sophisticated visual observation skills which enable them to visually search relevant features of a stimulus within irrelevant features and to interpret these observations correctly (e.g., Antes and Kristjanson 1991;Charness et al 2001;Jarodzka et al 2010a; Underwood et al 2003). Novices, however, get easily distracted by salient, but potentially irrelevant, elements of a visual stimulus, whilst missing relevant information (Jarodzka et al 2010a;Lowe 1999).…”
Section: Role Of Visual Observations In Clinical Reasoningmentioning
confidence: 99%
“…These studies showed that experts possess sophisticated visual observation skills which enable them to visually search relevant features of a stimulus within irrelevant features and to interpret these observations correctly (e.g., Antes and Kristjanson 1991;Charness et al 2001;Jarodzka et al 2010a; Underwood et al 2003). Novices, however, get easily distracted by salient, but potentially irrelevant, elements of a visual stimulus, whilst missing relevant information (Jarodzka et al 2010a;Lowe 1999).…”
Section: Role Of Visual Observations In Clinical Reasoningmentioning
confidence: 99%
“…So, bridge experts pay attention to the number of cards in each suit which is closely related to winning. Novices track the number of aces played which is easier to remember but less relevant to winning (Charness et al 2001). Similarly, physics experts rely on general laws like conservation of momentum to solve problems while novices concentrate on superficial features like whether the problem involves a spring or a plane (Chi et al 1981).…”
Section: Top Management Teams and Strategy As Simple Rulesmentioning
confidence: 99%
“…We were not surprised that video research imposed minimal attentional distraction on teachers, given the pressured, sophisticated and unpredictable nature of classroom teaching (e.g., Berliner, 2001). Compared with the research targets, non-research classroom regions possessed unmatched relevance (Charness, Reingold, Pomplun & Stampe, 2001;Foulsham & Kingstone, 2012) to teachers as they carried out their tasks of classroom instruction.…”
Section: Change In Teacher Reactivity Over Timementioning
confidence: 96%